Error of Beginnings and the Beginning of Errors: Creation and the Origin of the Universe - William E. Carroll (Studium: Filosofía y Teología)
Contemporary cosmological theories, from the singularity of the Big Bang, to quantum tunnelling from nothing, to various multiverse scenarios, have been the source of wide-ranging speculations about the creation of the universe. Some thinkers see the Big Bang as support for, if not confirmation of, the traditional doctrine of creation out-of-nothing. Others, who argue for an eternal series of big bangs, or view time itself as an emergent property in an already existing cosmos, or who think that science itself can account for the coming into existence of the world out of a primal nothing, conclude that cosmology now shows us that references to a creator are irrelevant. Such references are, in these views, artefacts from a less enlightened age. Most of the discussion about what cosmology tells us about creation suffers from a fundamental error about a necessary connection between the universe’s being created and its having a temporal beginning. This is an error of beginnings, which is the beginning of many other errors. It was the genius of Thomas Aquinas (1224-1274) to point out this error and to offer a sophisticated discussion about the relationship among cosmology, philosophy, and theology concerning the ultimate origin of the universe. Thomas’s analysis can help to resolve confusion in contemporary discussions about cosmology, the origin of the universe, and creation.